PELATIHAN DAN PENDAMPINGAN PENINGKATAN KINERJA USAHA BERBASIS STRATEGI DAN IT PADA PELAKU UMKM HASIL OLAHAN LAUT DI DESA LABUAN PANDEGLANG - BANTEN - Richo Rianto; Choiroel Woestho (Jurnal Pengabdian kepada Masyarakat UBJ, 2022)
The purpose of this community service is to provide education, training, and assistance in improving strategy and IT-based business performance for seafood MSME in the village of Labuan Banten. This training focuses on solving product problems that do not have Branding, and packaging, are not hygienic, do not have traditional sales and marketing strategies, and have low average sales. Solutions for the problem are training and assistance in Branding and packaging strategies, as well as the use of digital marketing, which are alternative solutions to problems in the short term to improve the performance of seafood MSME in Labuan village. It is hoped that after this activity is carried out, the MSME can have strong Branding, good packaging and a wide range of buyers and in the end can directly increase sales and indirectly help the regional economy and families.